Erythropoietin relieves neuronal apoptosis in epilepsy rats via TGF-β/Smad signaling pathway: Erythropoietin relieves nerve cell apoptosis in epilepsy rats - Pan, Xiaoxiao; Gong, Xiaoqian; Pan, Lili; Lu, Liyu (Cellular and Molecular Biology, 2023)
This study aimed to investigate the influence of recombinant human erythropoietin (rHuEPO) on pentylenetetrazol (PTZ)-induced neuronal apoptosis in epilepsy rats, and to explore the signaling pathways related to the action. Healthy Sprague-Dawley rats aged 8 weeks old were randomly divided into 5 groups, namely, control group, PTZ model group, PTZ + rHuEPO intervention group, PTZ + SB431542 + rHuEPO intervention group and PTZ + SB431542 (TGF-β/Smad inhibitor) intervention group. The expressions of apoptotic proteins [tumor necrosis factor receptor 1 (TNFR1) and caspase-3] and the transforming growth factor-beta (TGF-β)/Smad signaling pathway-related proteins [phosphorylated smad3 (p-smad3) and TGF-β1] in the brain tissues were determined via Western blotting (WB). Epilepsy was successfully induced by PTZ in the rats. The results of the TUNEL assay showed that the intervention with rHuEPO could remarkably reduce the number of PTZ-induced apoptotic neurons in the hippocampus, while SB431542 inhibitor could attenuate the protective effect of rHuEPO against neuronal apoptosis (P<0.05). In addition, the intraperitoneal injection of 50 μg/kg rHuEPO could activate the TGF-β/Smad signaling pathway, markedly up-regulate the expressions of TGF-β1 and p-smad3 (P<0.05), down-regulate the expressions of apoptotic proteins TNFR1 and caspase-3 (P<0.01) and reduce neuronal apoptosis. Moreover, SB431542 was able to notably repress the protective effect of rHuEPO against neuronal apoptosis, and down-regulate the expressions of p-smad3 and TGF-β1 (P<0.01). In conclusion, the inhibitory effect of rHuEPO on nerve cell apoptosis in epilepsy rats may be realized by activating the TGF-β/Smad signaling pathway, thus relieving neuronal apoptosis and ameliorating the symptoms of epilepsy.